Genetic variation of ABCB1 (rs1128503, rs1045642) and CYP2E1 rs3813867 with the duration of tuberculosis therapy: a pilot study among tuberculosis patients in Indonesia - Barliana, Melisa Intan (BMC Res Notes, 2021)
OBJECTIVE: The risk of contracting tuberculosis (TB) and the efficacy of TB therapy are affected by several factors, including genetic variation among populations. In the Indonesian population, data on the genes involved in drug transport and metabolism of TB therapy are limited. The aim of this study was to identify the genetic profile of the ABCB1 gene (rs1128503 and rs1045642) and CYP2E1 gene (rs3813867) in Indonesians with TB. This study was a cross-sectional study of 50 TB outpatients in Jambi city, Indonesia. Sociodemographic characteristics were obtained from medical records. Whole blood was collected, and genomic DNA was isolated. Single nucleotide polymorphisms were determined using polymerase chain reaction-restriction fragment length polymorphism with HaeIII, MboI, and PstI for rs1128503, rs1045642 (ABCB1), and rs3813867 (CYP2E1), respectively. RESULT: The frequency of alleles of each gene was analyzed by Hardy–Weinberg equilibrium. The genetic profiles of ABCB1 rs1128503 and rs1045642 were varied (CC, CT, TT), while CYP2E1 rs3813867 was present in CC (wild type). The genetic variations of ABCB1 and CYP2E1 may have no significant correlation with the duration of TB therapy. Nevertheless, this study may provide as preliminary results for the genetic profiles of ABCB1 (rs1128503, rs1045642) and CYP2E1 (rs3813867) in the Indonesia population. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13104-021-05711-8.